2011
DOI: 10.2169/internalmedicine.50.5335
|View full text |Cite
|
Sign up to set email alerts
|

Mantle Cell Lymphoma Mainly Involving Thoracic Lesions: Two Case Reports

Abstract: Most mantle cell lymphoma patients show remarkable disseminated disease at the initial diagnosis. We describe two cases of mantle cell lymphoma mainly involving thoracic lesions at the initial presentation of the disease. The clinical presentations were right hilar lymphadenopathy in one case and right pleural thickness in the other. The diagnosis of mantle cell lymphoma was confirmed by immunohistochemistry, including CD5, CD 20, and cyclin D1, and the presence of t(11 ; 14)(q13 ; q32) by fluorescence in situ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…One case in Chinese literature (6) was primary pleural small B-cell lymphocytic lymphoma, diagnosed by pleural mass biopsy. Two cases of mantle cell lymphoma mainly involving thoracic lesions as the initial presentation had also been reported in previous studies (7). But it is unique in our case that the diagnosis was initial confirmed by flow cytometry of pleural effusion, which showed that the abnormal B cells were marginal zone B cell phenotype.…”
Section: Introductionsupporting
confidence: 71%
“…One case in Chinese literature (6) was primary pleural small B-cell lymphocytic lymphoma, diagnosed by pleural mass biopsy. Two cases of mantle cell lymphoma mainly involving thoracic lesions as the initial presentation had also been reported in previous studies (7). But it is unique in our case that the diagnosis was initial confirmed by flow cytometry of pleural effusion, which showed that the abnormal B cells were marginal zone B cell phenotype.…”
Section: Introductionsupporting
confidence: 71%